2021
DOI: 10.48550/arxiv.2106.02063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlated insulators, semimetals, and superconductivity in twisted trilayer graphene

Maine Christos,
Subir Sachdev,
Mathias S. Scheurer

Abstract: Motivated by recent experiments indicating strong superconductivity and intricate correlated insulating and flavor-polarized physics in mirror-symmetric twisted trilayer graphene, we study the effects of interactions in this system close to the magic angle, using a combination of analytical and numerical methods. We identify asymptotically exact correlated many-body ground states at all integer filling fractions ν of the flat bands. To determine their fate when moving away from these fine-tuned points, we appl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 64 publications
4
31
0
Order By: Relevance
“…We predict that this velocity renormalization leads to an increase of the slow and decrease of the fast Dirac velocity in TTG. We remark that a U(1) generalization of our Gross-Neveu theory would correspond to intervalley coherent order in TTG 34 , which is expected to display qualitatively similar behavior to the velocity renormalization and critical exponents we have found based on studies of the XY-Gross-Neveu model 35,[56][57][58][59][60][61] . The generalization of our theory to experimentally relevant 17,18 twisted pentalayar graphene and other van-der-Waals materials with more than two Dirac velocities is left for future work.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…We predict that this velocity renormalization leads to an increase of the slow and decrease of the fast Dirac velocity in TTG. We remark that a U(1) generalization of our Gross-Neveu theory would correspond to intervalley coherent order in TTG 34 , which is expected to display qualitatively similar behavior to the velocity renormalization and critical exponents we have found based on studies of the XY-Gross-Neveu model 35,[56][57][58][59][60][61] . The generalization of our theory to experimentally relevant 17,18 twisted pentalayar graphene and other van-der-Waals materials with more than two Dirac velocities is left for future work.…”
supporting
confidence: 70%
“…26 Theoretically, different candidate states for a gap opening at charge neutrality in TBG have similar energies. [27][28][29][30][31][32][33] Among them, (sublattice-polarized) quantum valley Hall or intervalley coherent order have also been discussed to gap out the slow bands in TTG, based on extensions of the effective, exactly soluble models from TBG to TTG 34 .…”
mentioning
confidence: 99%
“…We should stress regarding the appropriateness of the approximation in Eq. (29). When the band structure resulting from this approximation was compared to band structures resulting from a full extended space treatment of the time dependent problem such as in [60] it was found that even at driving strengths as high as η = AaAA = 4 the approximation yielded results that were almost indistinguishable from the exact extended space treatment.…”
Section: B Numerical Resultsmentioning
confidence: 97%
“…In fact, it has been discovered that at certain, so-called magic angles, flat energy bands occur which then give rise to a plethora of highly correlated phases. An exciting example is a superconducting phase that occurs at the first magic twist angle [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. This superconducting state was first discovered in a land-mark paper in Nature Physics [20].…”
Section: Introductionmentioning
confidence: 99%
“…Strong-coupling superconductivity can arise from repulsive interactions, as a result of enhanced fluctuations near insulating ordered phases driven by these interactions. This picture has been extensively discussed in connection to the superconducting cuprates [18], pnictides [19][20][21], and also twisted bilayer graphene and other graphitic systems [22][23][24][25][26][27][28][29][30][31][32]. Superconductivity can also arise from repulsive interactions through virtual transition of electron pairs from the Fermi surface to distant or incipient bands [33,34].…”
Section: Introductionmentioning
confidence: 99%